2011
DOI: 10.1007/s00422-011-0457-3
|View full text |Cite
|
Sign up to set email alerts
|

Experimental analysis and computational modeling of interburst intervals in spontaneous activity of cortical neuronal culture

Abstract: Rhythmic bursting is the most striking behavior of cultured cortical networks and may start in the second week after plating. In this study, we focus on the intervals between spontaneously occurring bursts, and compare experimentally recorded values with model simulations. In the models, we use standard neurons and synapses, with physiologically plausible parameters taken from literature. All networks had a random recurrent architecture with sparsely connected neurons. The number of neurons varied between 500 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 46 publications
1
28
0
2
Order By: Relevance
“…To simulate the firing activity, we used a (pulse-coupled) spiking neural network model as described in Gritsun et al (2010Gritsun et al ( , 2011. We used a set of neuronal parameters that adequately reproduced the dynamics of cortical neurons (Izhikevich 2003), for details see "Neuron model."…”
Section: Computer Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…To simulate the firing activity, we used a (pulse-coupled) spiking neural network model as described in Gritsun et al (2010Gritsun et al ( , 2011. We used a set of neuronal parameters that adequately reproduced the dynamics of cortical neurons (Izhikevich 2003), for details see "Neuron model."…”
Section: Computer Modelingmentioning
confidence: 99%
“…To validate the solidity of our findings, we repeated all experiments in multiple simulations, based on different network realizations (different set of neurons and a different connectivity matrix), different noise realizations (with the same stochastic characterization), and different STDP models (see "Synaptic noise and model sensitivity"). A more thorough sensitivity analysis of this type of models can be found in Gritsun et al (2010Gritsun et al ( , 2011Gritsun et al ( , 2012. The model was implemented in Matlab and C++, codes are available upon request.…”
Section: Computer Modelingmentioning
confidence: 99%
“…Previous modeling efforts have shown that synchronous activity is a common phenomenon in simulated neuronal networks and have studied how individual neuronal and synaptic dynamics affect synchronization (BΓΆrgers and Kopell, 2003; Kudela et al, 2003; Kube et al, 2004; Belykh et al, 2005; Nesse et al, 2008). Recent work has also focused on studying the importance of network level parameters such as axonal delays, ratio of excitatory/inhibitory neurons (E/I ratio), and the maximum number of connections (Gritsun et al, 2010, 2011) through simulation of networks with pacemaker neurons and random connections. Here, we extend this work by studying the emergence of synchronized bursting in networks without inherent pacemaker neurons, and with variable densities and small-world connections.…”
Section: Introductionmentioning
confidence: 99%
“…Π’ соврСмСнных Ρ€Π°Π±ΠΎΡ‚Π°Ρ… ΠΏΠΎ ΠΈΠ·ΡƒΡ‡Π΅Π½ΠΈΡŽ элСктрофизиологичСской активности Π½Π΅ΠΉΡ€ΠΎΠ½Π°Π»ΡŒΠ½Ρ‹Ρ… ΠΊΡƒΠ»ΡŒΡ‚ΡƒΡ€ in vitro особоС Π²Π½ΠΈΠΌΠ°Π½ΠΈΠ΅ удСляСтся Ρ„Π΅Π½ΠΎΠΌΠ΅Π½Ρƒ спонтанной ΠΏΠ°Ρ‡Π΅Ρ‡Π½ΠΎΠΉ активности [1][2][3][4][5][6][7][8][9][10]. ΠŸΠΎΠΏΡƒΠ»ΡΡ†ΠΈΠΎΠ½Π½ΠΎΠΉ ΠΏΠ°Ρ‡ΠΊΠΎΠΉ (ΠΈΠ»ΠΈ просто ΠΏΠ°Ρ‡ΠΊΠΎΠΉ) активности ΠΊΡƒΠ»ΡŒΡ‚ΡƒΡ€Ρ‹ называСтся явлСниС Ρ€Π΅Π·ΠΊΠΎΠ³ΠΎ возрастания активности Π³Ρ€ΡƒΠΏΠΏ Π½Π΅ΠΉΡ€ΠΎΠ½ΠΎΠ² Π² Ρ‚Π΅Ρ‡Π΅Π½ΠΈΠ΅ ΠΊΠΎΡ€ΠΎΡ‚ΠΊΠΎΠ³ΠΎ ΠΏΡ€ΠΎΠΌΠ΅ΠΆΡƒΡ‚ΠΊΠ° Π²Ρ€Π΅ΠΌΠ΅Π½ΠΈ.…”
Section: Introductionunclassified
“…Π’ Ρ€Π°Π±ΠΎΡ‚Π΅ [8] ΠΏΡ€ΠΎΠΈΠ·Π²Π΅Π΄Π΅Π½ΠΎ сравнСниС характСристик ΠΏΠ°Ρ‡Π΅Ρ‡Π½ΠΎΠΉ активности ΠΊΡƒΠ»ΡŒΡ‚ΡƒΡ€ Π½Π΅ΠΉΡ€ΠΎΠ½ΠΎΠ² in vitro, Ρ‚Π°ΠΊΠΈΡ… ΠΊΠ°ΠΊ Π΄Π»ΠΈΡ‚Π΅Π»ΡŒΠ½ΠΎΡΡ‚ΡŒ ΠΏΠ°Ρ‡Π΅ΠΊ ΠΈ пиковая Π°ΠΌΠΏΠ»ΠΈΡ‚ΡƒΠ΄Π° суммарной активности Π½Π΅ΠΉΡ€ΠΎΠ½ΠΎΠ² Π²Π½ΡƒΡ‚Ρ€ΠΈ ΠΏΠ°Ρ‡ΠΊΠΈ, с Π°ΠΊΡ‚ΠΈΠ²Π½ΠΎΡΡ‚ΡŒΡŽ ΠΌΠΎΠ΄Π΅Π»ΠΈ ΠΊΡƒΠ»ΡŒΡ‚ΡƒΡ€Ρ‹ Π½Π΅ΠΉΡ€ΠΎΠ½ΠΎΠ² Π² ΡˆΠΈΡ€ΠΎΠΊΠΎΠΌ Π΄ΠΈΠ°ΠΏΠ°Π·ΠΎΠ½Π΅ измСнСния Π²Π½ΡƒΡ‚Ρ€Π΅Π½Π½ΠΈΡ… ΠΏΠ°Ρ€Π°ΠΌΠ΅Ρ‚Ρ€ΠΎΠ² ΠΌΠΎΠ΄Π΅Π»ΠΈ. Π’ Ρ€Π°Π±ΠΎΡ‚Π΅ [9], ΡΠ²Π»ΡΡŽΡ‰Π΅ΠΉΡΡ ΠΏΡ€ΠΎΠ΄ΠΎΠ»ΠΆΠ΅Π½ΠΈΠ΅ΠΌ Ρ€Π°Π±ΠΎΡ‚Ρ‹ [8], Π²Π½ΠΈΠΌΠ°Π½ΠΈΠ΅ ΡƒΠ΄Π΅Π»Π΅Π½ΠΎ Π°Π½Π°Π»ΠΈΠ·Ρƒ ΠΌΠ΅ΠΆΠΏΠ°Ρ‡Π΅Π½Ρ‹Ρ… ΠΈΠ½Ρ‚Π΅Ρ€Π²Π°Π»ΠΎΠ² -ΠΏΠ΅Ρ€ΠΈΠΎΠ΄Π°ΠΌ Π²Ρ€Π΅ΠΌΠ΅Π½ΠΈ ΠΌΠ΅ΠΆΠ΄Ρƒ популяционными ΠΏΠ°Ρ‡ΠΊΠ°ΠΌΠΈ активности, Π²Ρ‹ΡΠ²Π»Π΅Π½ΠΈΡŽ ΠΏΠ°Ρ€Π°ΠΌΠ΅Ρ‚Ρ€ΠΎΠ² ΠΌΠΎΠ΄Π΅Π»ΠΈ ΠΊΡƒΠ»ΡŒΡ‚ΡƒΡ€Ρ‹ Π½Π΅ΠΉΡ€ΠΎΠ½ΠΎΠ², ΠΊΠΎΡ‚ΠΎΡ€Ρ‹Π΅ ΠΏΠΎΠ·Π²ΠΎΠ»ΡΡŽΡ‚ Π΄ΠΎΡΡ‚ΠΈΡ‡ΡŒ Π½Π°ΠΈΠ»ΡƒΡ‡ΡˆΠ΅Π³ΠΎ соотвСтствия с Π΄Π°Π½Π½Ρ‹ΠΌΠΈ ΠΎ распрСдСлСнии ΠΌΠ΅ΠΆΠΏΠ°Ρ‡Π΅Ρ‡Π½Ρ‹Ρ… ΠΈΠ½Ρ‚Π΅Ρ€Π²Π°Π»ΠΎΠ² ΠΊΡƒΠ»ΡŒΡ‚ΡƒΡ€ Π½Π΅ΠΉΡ€ΠΎΠ½ΠΎΠ² in vitro. Однако, нСсмотря Π½Π° ΡˆΠΈΡ€ΠΎΠΊΠΈΠΉ ΠΊΡ€ΡƒΠ³ исслСдований Π² области Π²Ρ‹Ρ‡ΠΈΡΠ»ΠΈΡ‚Π΅Π»ΡŒΠ½Ρ‹Ρ… Π½Π΅ΠΉΡ€ΠΎΠ½Π°ΡƒΠΊ, ΠΏΡ€ΠΈΠ΅ΠΌΠ»Π΅ΠΌΠΎΠΉ ΠΌΠΎΠ΄Π΅Π»ΠΈ Ρ„Π΅Π½ΠΎΠΌΠ΅Π½Π° ΠΏΠ°Ρ‡Π΅Ρ‡Π½ΠΎΠΉ активности, ΠΏΠΎΠ·Π²ΠΎΠ»ΡΡŽΡ‰Π΅ΠΉ ΠΏΠΎΠ»ΡƒΡ‡ΠΈΡ‚ΡŒ ΠΏΠΎΠ»Π½ΠΎΠ΅ согласованиС активности ΠΌΠΎΠ΄Π΅Π»ΠΈ с Π°ΠΊΡ‚ΠΈΠ²Π½ΠΎΡΡ‚ΡŒΡŽ ΠΊΡƒΠ»ΡŒΡ‚ΡƒΡ€Ρ‹ in vitro, ΠΏΠΎΠΊΠ° Π½Π΅ сущСствуСт.…”
Section: Introductionunclassified